Verification Of The Behavior Of The Auditory Organ To The Industrial Professional Noise In The Boiler And Forging Rooms At "Nicolina Mechanical Plant" - Gabriel Drug; Viorica Gavat (Romanian Society of Oral Rehabilitation, 2011)
The symptomatology of the professional acoustic trauma varies according to the stage of the clinical observation, even if at the first contacts with the noise the workers signal the sensation of muffled hearing, various ringing sounds, etc. The present study aims at checking the behavior of the auditory organ to the industrial professional noise through experimental research conducted at the boiler and forging rooms of "Nicolina Mechanical Plant". Clinic and experimental: the lot of patients totaled 14 witness subjects, aged between 18 - 25, without hearing disorder history, with normal otoscopic aspect and unimpaired hearing in order to determine the audiometric behavior in relation to the professional noise. The symptoms fade away after work is finished. After 8-10 days there appears a phenomenon of adaptation with disappearance of the symptoms. Deafness occurs silently, varying from one subject to another depending on the individual type, ranging from several months to a couple of years.